2014
DOI: 10.1515/jpem-2013-0322
|View full text |Cite
|
Sign up to set email alerts
|

A teenage boy with hypocalcemia after radioablation for Graves’ disease

Abstract: Excessive thyroid hormone production, as seen in Graves' disease, stimulates osteoblast-mediated bone turnover in favor of bone resorption. Acute reversal of bone resorption can lead to hungry bone syndrome (HBS), a state of rapid calcium deposition into newly synthesized osteoid resulting in hypocalcemia. Hypocalcemia due to subsequent functional or relative hypoparathyroidism is a recognized complication of therapy for Graves' disease. HBS is most recognized as an outcome of rapid correction of vitamin D def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…One mechanism of serum calcium fall, especially if the patient experienced thyrotoxicosisassociated hypercalcemia, is increased osteoblastic activity, bone formation being more exacerbated than bone resorption after normalization of thyroid status. Excessive thyroid hormones cause an elevation of osteoblast-derivate bone turnover favoring the resorption while acute drop of these hormones causes a prompt reversal of bone resorption, newly synthesized osteoid being "hungry" to deposit calcium which leads to hypocalcemia [167][168][169][170][171]. Lazareva et al reported a teenager with Basedow's disease who developed HBS after radioiodine ablation [171].…”
Section: Integrating Ptx-related Hbs To Non-ptx Causes Of Hbsmentioning
confidence: 99%
See 1 more Smart Citation
“…One mechanism of serum calcium fall, especially if the patient experienced thyrotoxicosisassociated hypercalcemia, is increased osteoblastic activity, bone formation being more exacerbated than bone resorption after normalization of thyroid status. Excessive thyroid hormones cause an elevation of osteoblast-derivate bone turnover favoring the resorption while acute drop of these hormones causes a prompt reversal of bone resorption, newly synthesized osteoid being "hungry" to deposit calcium which leads to hypocalcemia [167][168][169][170][171]. Lazareva et al reported a teenager with Basedow's disease who developed HBS after radioiodine ablation [171].…”
Section: Integrating Ptx-related Hbs To Non-ptx Causes Of Hbsmentioning
confidence: 99%
“…Excessive thyroid hormones cause an elevation of osteoblast-derivate bone turnover favoring the resorption while acute drop of these hormones causes a prompt reversal of bone resorption, newly synthesized osteoid being "hungry" to deposit calcium which leads to hypocalcemia [167][168][169][170][171]. Lazareva et al reported a teenager with Basedow's disease who developed HBS after radioiodine ablation [171]. Post-thyroidectomy hypocalcemia, on the other hand, may be caused by transitory or permanent hypoparathyroidism, being described with a much more important epidemiological impact than other complications [172].…”
Section: Integrating Ptx-related Hbs To Non-ptx Causes Of Hbsmentioning
confidence: 99%
“…There are case reports about patients appearing hypocalcemia after RAI treatment as well. Oksana Lazareva [81] reported 16-year-old young male patients with Graves' disease was given 15mCi RAI for treatment. After 11 weeks, he had paralysis, muscle spasms, fatigue and discomfort.…”
Section: Effect Of Rai Treatment On Parathyroid Function For Benign Thyroid Diseasementioning
confidence: 99%